2023
DOI: 10.3390/jcm12041321
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Body Composition and Sarcopenia on Mortality in Chronic Obstructive Pulmonary Disease Patients

Abstract: Background: Patients with chronic obstructive pulmonary disease (COPD) have alterations in body composition, such as low cell integrity, body cell mass, and disturbances in water distribution evidenced by higher impedance ratio (IR), low phase angle (PhA), as well as low strength, low muscle mass, and sarcopenia. Body composition alterations are associated with adverse outcomes. However, according to the European Working Group on Sarcopenia in Older People 2 (EWGSOP2), the impact of these alterations on mortal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…The research also describes that the phase angle reduces with age regardless of body composition [36]. Gómez-Martínez et al showed PhA < 5.1 • in men and <4.8 • in women was independently associated with mortality in patients with Chronic Obstructive Pulmonary Disease Patients (COPD) [37]. Low phase angle in COPD patients (<4.5 • ) was also associated with lower quadricep strength and quality of life [38].…”
Section: Discussionmentioning
confidence: 99%
“…The research also describes that the phase angle reduces with age regardless of body composition [36]. Gómez-Martínez et al showed PhA < 5.1 • in men and <4.8 • in women was independently associated with mortality in patients with Chronic Obstructive Pulmonary Disease Patients (COPD) [37]. Low phase angle in COPD patients (<4.5 • ) was also associated with lower quadricep strength and quality of life [38].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, specific KCL subdomains that demonstrated the strongest correlation with hippocampal volume were identified through questions (1-5), (6)(7)(8)(9)(10), and (16)(17). The first five questions, designated as KCL (1)(2)(3)(4)(5), pertain to instrumental activities of daily living (IADL), assessing the ability to execute daily tasks that demand both cognitive and physical capabilities. Questions (6-10) focus on physical strength and evaluate the individual's muscular and physical endurance.…”
Section: Discussionmentioning
confidence: 99%
“…Each subdomain reached an area under the curve (AUC) of 0.78, indicating reliability. Specifically, achieving a score of 13 or higher or a score of 6 or higher in the KCL overall domain (1-25) and the KCL sub-domain (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), respectively, resulted in a specificity of 93% and a sensitivity of 90%. In the KCL subdomains (1-5) and (6-10), a score of 2 or higher or a score of 3 or more, respectively, resulted in a sensitivity of 80% and a specificity of 87%, and a score of 1 or higher in the KCL subdomain (16)(17) attained 83% specificity in detecting individuals within the lowest quartile.…”
Section: Or Peer Review 5 Of 12mentioning
confidence: 99%
“…However, there are clear differences in morphofunctional values with a decrease in PhA in the survival vs. non-survival groups (4.85 • vs. 4.27 • p = 0.033) according to BIVA. Gómez-Martínez et al showed that low PhA (5.11 • vs. 4.62 • , p = 0.008) was independently associated with a worse prognosis for COPD patients [33]. Machado et al showed that a quarter of IPF patients with a normal to obese BMI had abnormally low PhA, and patients with IPF classified as low-PhA had worse lung function, exercise capacity, and HRQL [34].…”
Section: Discussionmentioning
confidence: 99%